Wealth Inequality and Homeownership in Europe - Leo Kaas; Georgi Kocharkov; Edgar Preugschat (Center for Economic Studies and ifo Institute (CESifo), 2015)
The recently published Household Finance and Consumption Survey has revealed large differences in wealth inequality between the countries of the Euro area. We find a strong negative correlation between wealth inequality and homeownership rates across countries. We use two decomposition methods to shed more light on this correlation. First, a Gini decomposition by homeownership status shows that the negative relationship is mostly driven by large between-group inequality across owners and renters. Second, to control for other observables, we conduct a detailed counterfactual decomposition of crosscountry inequality differences. We confirm the major role for homeownership rates in accounting for the wealth inequality differences. Our analysis suggests that the cross-country variation is mostly driven by differences in the savings behavior of households in the bottom half of the wealth distribution and that those differences in savings are to a large extent channeled through housing wealth.
Keywords: D31; E21; G11; 330; wealth inequality; homeownership; housing; Euro area